Molecular and Immunological Detection of Hepatitis C Virus in Patients with Chronic Renal Failure - Abdulameer, Hala B.; Ismael, May K. (Iraqi Journal of Science, 2024)
Due to its association with hepatocellular carcinoma and being one of the ten most common malignancies worldwide, hepatitis C viral infection has become a severe public health concern. Therefore, establishing an accurate, reliable and sensitive diagnostic test for this infection is strongly advised. Real-time polymerase chain reaction (PCR) has been created to achieve this purpose. The current study was established to investigate the hepatitis C virus among Iraqi patients with chronic renal failure and to detect the virus immunologically by the fourth generation enzyme-linked immunosorbent assay technique and molecularly by real-time PCR. As a result, out of 50 patients with chronic renal failure undergoing dialysis, 39 patients tested positive for anti-HCV IgG by ELISA test and only 9 patients of the total count tested positive and showed growth curves with copy numbers of 1×102, 2.5×102, 3×102, 2.7×103, 2.7×103, 3.5×103, 8.7×104, 3.5×105 and 5.5×106 copies/ml respectively detected for HCV only by real-time PCR. Therefore, real-time PCR is beneficial for precise viral load determination and detection of viral hepatitis in chronic renal failure patients.